PENERAPAN PROGRAM PEMBELAJARAN SHOW AND TELL DALAM GERAKAN LITERASI SEKOLAH DI SD MUHAMMADIYAH CONDONGCATUR - Yanti, Gusti; Suyatno, Suyatno (universitas Ahmad Dahlan, 2018)
This study aims to describe 1) the urgency of thelearning program show and tell in the literacy movement at SD Muhammadiyah Condongcatur; 2) the application oflearning programs show and tell in the literacy movement at SD Muhammadiyah Condongcatur; 3) supporting and inhibiting factors for thelearning program show and tell in the literacy movement at SD Muhammadiyah Condongcatur.This type of research uses qualitative descriptive research. This research is the vice principal, teachers, students, and library officers. Data collection uses triangulation techniques and sources. The data analysis techniques use Model Miles and Huberman.The results of the study can be summarized as follows. 1) The urgency of thelearning program show and tell in the literacy movement at SD Muhammadiyah Condongcatur is very important students due tolearning show and tell train students to understand what information is read, then convey, have information to make products, add insight, share information, and train self-confidence. 2) Application oflearning show and tell through 3 stages, namely planning, implementation, and evaluation. 3) Factors supporting learninghow and tell, among others, principals support the success oflearning programs show and tell, competent subject teachers, and enthusiasm in implementinglearning programs show and tell, schools provide adequate facilities and infrastructure, students are active subjects inlearning show and tell. The inhibiting learning show and tell factor include lack of time, with teacher supervision and there is no readiness of students when they turn to show and tell.